PARTISIPASI ANGGOTA PAGUYUBAN “HARAPAN MULYA” PENGOLAH IKAN DALAM REALISASI PROGRAM BANTUAN LANGSUNG MASYARAKAT PENGEMBANGAN USAHA MINA PERDESAAN PERIKANAN BUDIDAYA (BLM-PUMP PB) DI KECAMATAN GODEAN KABUPATEN SLEMAN - Nindiya Baggaswara; Vini Arumsari; Teguh Kismantoroadji (Jurnal Dinamika Sosial Ekonomi, 2015)
This research objective is to know the participation of "Harapan Mulya" association members participation on realization of "Program Bantuan Langsung Masyarakat Pengembangan  Usaha  Mina  Pedesaan",  to  analize  the  influence  of  age,  education, experience and mentoring factor on participation level on realization of "Program Bantuan Langsung Masyarakat - Pengembangan Usaha Mina Pedesaan", to identify any constrains faced by "HARAPAN MULYA" Association on realization of "Program Bantuan Langsung Masyarakat.  -  Pengembangan  Usaha  Mina  Pedesaan.  Implementation  method  of  this research using survei method. Research location determination was using purposive method. As for sampling method are using sensus method. Data used for this researh are primary and secondary  data. Data collection technique using observation, interview, and questionaire. As for analizing the influence of age, education, experience and mentoring are using double linear regression analysis. The research results shows that the factors that controlling participation level of "HARAPAN MULYA" association members are age, experience, education and mentoring. Participation level of "HARAPAN MULYA" association members on Program Bantuan Langsung Masyarakat - Pengembangan Usaha Mina Perdesaan Perikanan Budidaya is medium. Constraints faced during the program running are lack of ptomotion, so that the new Culinary Market Eel lack of visitors and causing income decrease for the eel chip merchant on that market. This income decrease complained by all eel chip merchant. The relocated of the market with the layout according to merchant less precise. Companion role in determining the production cost and the market price has not been determined yet optimal. Keywords : Participation, Program Bantuan Langsung Masyarakat - Pengembangan Usaha Mina Pedesaan, Harapan Mulya Association.